2004
DOI: 10.1002/cncr.11944
|View full text |Cite
|
Sign up to set email alerts
|

Gamma radiation sensitivity and risk of malignant and benign salivary gland tumors

Abstract: A general model for predicting the thermophysical properties of refrigerant/lubricant mixtures has been developed based on applicable theory for the excess Gibbs energy of nonideal solutions. In our approach, flexible thermodynamic forms are chosen to describe the properties of both the gas and liquid phases of refrigerant/lubricant mixtures. After an extensive study of models for describing nonideal liquid effects, the Wohl [3]‐suffix equations, which have been extensively used in the analysis of hydrocarbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Ionizing radiation and direct contact with asbestos are environmental risk factors for the development of salivary gland neoplasms. 3 In addition, Milena et al 4 reported that the presence of CMV antigens in different histological types of Salivary gland carcinoma (SGC) may play an important role in carcinogenesis by increasing IL-6 production, inhibiting apoptosis and inducing tumor development. Bianca et al 1 also suggested that the expression of apoptosis-regulating miRNAs in salivary gland tumors is associated with salivary gland tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Ionizing radiation and direct contact with asbestos are environmental risk factors for the development of salivary gland neoplasms. 3 In addition, Milena et al 4 reported that the presence of CMV antigens in different histological types of Salivary gland carcinoma (SGC) may play an important role in carcinogenesis by increasing IL-6 production, inhibiting apoptosis and inducing tumor development. Bianca et al 1 also suggested that the expression of apoptosis-regulating miRNAs in salivary gland tumors is associated with salivary gland tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of salivary gland tumors is uncertain in humans; however, several studies have indicated radiation exposure as a risk factor . DNA damage from radiation causes chromosomal breaks and aberrations, which may predispose to tumor development . In NHPs, there is little research regarding radiation exposure and salivary gland tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings from our group showed that apoptosis capacity and DNA repair capacity in response to gamma irradiation were significantly reduced in patients with SGC. 13, 26 Experimental data revealed that BRCA1 modulates cellular susceptibility to apoptosis induced by gamma radiation, 27 and BRCA1 mutations slow the rate of repair of radiation-induced double-strand breaks. 28 BRCA1 is expressed in both acinar and ductal epithelial cells in the salivary gland, and its expression is correlated with proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this concept, we previously found reduced DNA repair capacity in SGC patients compared to cancer-free controls. 13 …”
Section: Introductionmentioning
confidence: 99%